2014
DOI: 10.4161/cc.28652
|View full text |Cite
|
Sign up to set email alerts
|

Mcm10 deficiency causes defective-replisome-induced mutagenesis and a dependency on error-free postreplicative repair

Abstract: Mcm10 is a multifunctional replication factor with reported roles in origin activation, polymerase loading, and replication fork progression. the literature supporting these variable roles is controversial, and it has been debated whether Mcm10 has an active role in elongation. Here, we provide evidence that the mcm10-1 allele confers alterations in DNA synthesis that lead to defective-replisome-induced mutagenesis (DRIM). Specifically, we observed that mcm10-1 cells exhibited elevated levels of pCNA ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 78 publications
2
27
0
Order By: Relevance
“…At higher temperatures, however, when cells accumulated more severe DNA damage (Becker et al, 2014), the majority of mcm10-1 and mcm10-1 slx5Δ mutants remained arrested in G2/M (Figure 6B), consistent with a more robust Rad53 activation observed at 35°C compared to 33°C (Figures 6C and D). Hyper-phosphorylation of Rad53 observed at 35°C in mcm10-1 mutants was slightly diminished when SLX5 was knocked out, implying that Slx5 contributes to checkpoint signaling under extreme DNA damage conditions (Figure 6D).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…At higher temperatures, however, when cells accumulated more severe DNA damage (Becker et al, 2014), the majority of mcm10-1 and mcm10-1 slx5Δ mutants remained arrested in G2/M (Figure 6B), consistent with a more robust Rad53 activation observed at 35°C compared to 33°C (Figures 6C and D). Hyper-phosphorylation of Rad53 observed at 35°C in mcm10-1 mutants was slightly diminished when SLX5 was knocked out, implying that Slx5 contributes to checkpoint signaling under extreme DNA damage conditions (Figure 6D).…”
Section: Resultssupporting
confidence: 65%
“…Heat-induced depletion of Mcm10 causes replication stress displaying the typical hallmarks of Rad53 phosphorylation and PCNA ubiquitination (Becker et al, 2014). SGA analysis identified SLX5 and SLX8 as top hits that exhibited synthetic sickness with the mcm10-1 allele at 30°C (Thu and Bielinsky, 2013, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contrary to the data generated in most single celled systems which suggest that Mcm10 is required for multiple stages of DNA replication (Thu and Bielinsky, 2013). Data from S. cerevisiae has demonstrated that DNA replication can occur in Mcm10 deficient backgrounds through a dependence on error-free post-replicative repair, although at the cost of higher mutation rates (Becker et al, 2014). The observed adult survivorship in these mutants does not necessarily equate to normal S-phase progression, the presence of endogenous chromatin states, or a natural rate of mutation accumulation.…”
Section: : Discussionmentioning
confidence: 99%
“…Current evidence supports the idea that Mcm10 travels with the processing replisome (Aparicio et al, 1997; Das-Bradoo et al, 2006), and modulates chromatin dynamics (Apger et al, 2010; Liachko and Tye, 2009). Mcm10 has also been demonstrated to promote genomic stability through extensive interplay with DNA damage repair mechanisms (Alver et al, 2014; Becker et al, 2014; Thu and Bielinsky, 2014). Despite the wealth of data describing the functions of Mcm10 in various steps in DNA metabolism, conflicting results between model systems have left the essential functions of Mcm10 highly debated (Thu and Bielinsky, 2013).…”
Section: : Introductionmentioning
confidence: 99%